2013
DOI: 10.1590/0004-282x20130037
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric multidetector computed tomography scanning on suspicion of hyperacute ischemic stroke: validating a standardized protocol

Abstract: Multidetector computed tomography (MDCT) scanning has enabled the early diagnosis of hyperacute brain ischemia. We aimed at validating a standardized protocol to read and report MDCT techniques in a series of adult patients. The inter-observer agreement among the trained examiners was tested, and their results were compared with a standard reading. No false positives were observed, and an almost perfect agreement (Kappa>0.81) was documented when the CT angiography (CTA) and cerebral perfusion CT (CPCT) map dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…All examinations were conducted with a previously reported institutional protocol 14 with a minimum dose of ionizing radiation and intravenous iodinated contrast in a Philips Brilliance 64-slice CT scanner (Brilliance CT 64 Channel, Philips Medical, Eindhoven, The Netherlands). The examinations included non-contrast computed tomography and cervical and intracranial MDCTA, which required up to 5 min.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…All examinations were conducted with a previously reported institutional protocol 14 with a minimum dose of ionizing radiation and intravenous iodinated contrast in a Philips Brilliance 64-slice CT scanner (Brilliance CT 64 Channel, Philips Medical, Eindhoven, The Netherlands). The examinations included non-contrast computed tomography and cervical and intracranial MDCTA, which required up to 5 min.…”
Section: Protocolmentioning
confidence: 99%
“…In addition, it is an accurate and powerful noninvasive tool for assessing carotid artery disease in the setting of hyperacute ischemic stroke, including the detection of atherosclerosis involvement in extra-and intra-cranial vessels. However, only a few studies have reported the use of MDCTA to define stroke etiology in our population 14 . To the best of our knowledge, MDCTA has not yet been used to study the etiology of stroke in a Latin American population.…”
mentioning
confidence: 97%
“…The interobserver agreement between Neuroradiology fellows was higher than between the general Radiology residents 5 . The paper also presents an important point to be discussed: the need of an adequate post-processing of CT perfusion and CT-angio.…”
Section: Referencesmentioning
confidence: 69%
“…In the paper from Pacheco et al 5 , there was no false negative diagnoses of acute ischemic stroke when the different CT techniques using a standardized reading protocol were associated. The definition of a standardized step-by-step interpretation in multiparametric multidetector CT in the evaluation of the signs of hyperacute stroke can aid in the detection of subtle signs of this type of lesion.…”
Section: Multimodal Multidetector Computed Tomography Scanning and Thmentioning
confidence: 97%
See 1 more Smart Citation